Chiral Photodetector Based on GaAsN. (22nd April 2021) - Joshya, Rajagopal Shyamala; Carrère, Hélène; Ibarra‐Sierra, Victor Guadalupe; Sandoval‐Santana, Juan Carlos; Kalevich, Vladimir K.; Ivchenko, Eugeniyus L.; Marie, Xavier; Amand, Thierry; Kunold, Alejandro; Balocchi, Andrea
Abstract: The detection of light helicity is key for various applications, from drug production to optical communications. However, the light helicity direct measurement is inherently impossible with conventional photodetectors based on III–V or IV–VI non‐chiral semiconductors. The prior polarization analysis by often moving optical elements is necessary before light is sent to the detector. A method is here presented to effectively give the conventional dilute nitride GaAs‐based semiconductor epilayer a chiral photoconductivity. The detection scheme relies on the giant spin‐dependent recombination of conduction electrons and the accompanying spin polarization of the engineered defects to control the conduction band. As the conduction electron spin polarization is, in turn, intimately linked to the excitation light polarization, the light polarization state and intensity can be determined by a simple conductivity measurement. This approach, removing the need for any optical elements in front of a non‐chiral detector, could offer easier integration and miniaturization. This new chiral photodetector could potentially operate in a spectral range from the visible to the infra‐red using (InGaAl)AsN alloys or ion‐implanted nitrogen‐free III–V compounds. Abstract : A novel scheme for a chiral detector based on GaAsN is demonstrated allowing for the simultaneous detection of the light intensity and degree of circular polarization at room temperature. It relies on the engineering of deep paramagnetic defects displaying a giant spin dependent recombination, effectively providing chirality to these conventional compounds and removing the need for any additional optical elements.